ISSUES OF ORGANIZING AUDIT UNDER CONDITIONS OF THE DIGITAL ECONOMY (British Journal of Global Ecology and Sustainable Development, 2023)
The article is devoted to the consideration of the issues of organizing audit activities in the digital economy. In addition, the article reveals the theoretical issues of the audit, its practice, methods used and audit process under the conditions of economy digitalization.